Application of the Rasch Model in the Development of Employee Performance Instruments - Setia Budi, Achmad Rizki; Hidayah, Fenti Nur; Sari, Widiah Ratna; Ragil, Muh.; Ardiansyah,, Fuad (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
Employee performance measurement is crucial because as a result as a means of evaluation, development and decision making in the organization. For this reason, the validity and reliability of employee performance instruments are determining factors to ensure that the data obtained is accurate or not. This research aims to develop and validate private employee performance instruments in the Southwest Papua region. This research was conducted using quantitative methods. The sampling technique used in this study was random sampling technique. The population in the study were private employees as many as 75 respondents who would be used in representing the population of respondents in Southwest Papua. In this study, the software used to analyze the data is Ministep Rasch to see the relationship between items and respondents. Based on the analysis, item 5 is difficult for respondents to agree and item 9 is easy for respondents to agree. This shows that the tool developed has good validity. In addition, there are results of the validity test of items 11, 10, 5, 12, 9 and item 4 that do not match (FIT model). Cronbach's Alpha value of 0.92 can be said to have a very good value related to items and people. This research was conducted by analyzing the results of difficulty (Item Difficulty), analyzing the level of fit on items or FIT (Item fit), and the level of reliability (item reliability).Pengukuran kinerja karyawan menjadi krusial karena sebagai hasil karena sebagai sarana evaluasi, pengembangan dan pengambilan keputusan dalam organisasi. Untuk itu, validitas dan reliabilitas instrumen kinerja karyawan menjadi faktor penentu untuk memastikan data yang diperoleh akurat atau tidaknya. Penelitian ini bertujuan untuk mengembangkan serta memvalidasi instrumen kinerja karyawan swasta di wilayah Papua Barat Daya. Penelitian ini dilakukan dengan menggunakan metode kuantitatif. Teknik pengambilan sampel yang digunakan pada penelitian ini adalah teknik random sampling. Populasi dalam penelitian adalah karyawan swasta sebanyak 75 responden yang akan digunakan dalam mewakili populasi responden di Papua Barat Daya. Pada penelitian ini perangkat lunak yang digunakan untuk menganalisis data yaitu Ministep Rasch untuk melihat hubungan pada item dan responden. Berdasarkan pada analisis terdapat item 5 sulit disetujui oleh responden dan item 9 mudah disetujui oleh responden. Hal ini menunjukkan alat yang dikembangkan memiliki validitas yang baik. Selain itu ada hasil uji validitas item 11,10, 5, 12, 9 dan item 4 tidak cocok dengan (model FIT). Nilai Alpha Cronbach 0,92 dapat dikatakan memiliki nilai bagus sekali terkait item dan person Penelitian ini dilakukan dengan menganalisis hasil kesukaran (Item Difficulty), analisis tingkat kesesuaian pada item atau FIT (Item fit), dan tingkat reliabilitas (item reliability). Dari hasil analisis yang sudah dilakukan pada instrumen kinerja karyawan termasuk dalam data valid dan reliabel dan dapat digunakan sebagai keperluan yang dibutuhkan seperti need asessment.